Examination of the Iraqi product lathe cut dental amalgam alloy by using Taha Indicator. Microscopic investigation - Lamia T Rejab; Nadia H Hasan; Munther N Kazanji (University of Mosul, College of Dentistry, 2004)
Many dental materials have been marketed locally in the last few years. The dentist should understand the selection principles that based on scientific tests to choose the product. Dental amalgam alloy is one of the dental materials that used in restorative dentistry for restoration decayed teeth. The primary objective of the study is to examine the lathe-cut Iraqi dental amalgam alloy (Al-Rafidain) microscopi-cally. The examination of alloy powder particles shape was made with transmitted light microscope using "Taha Indicator" instead of reflected light microscope or electron microscope. The results showed that the examina-tion with transmitted light microscope by using "Taha Indicator" give obvious and clear image of the alloy powder particles and also showed that Al-Rafidain amal-gam alloy powder has large and irregular shape particles that may give inferior physical properties to the product, so more evaluation and examination by other rela-ted tests may be needed.